Effect of Weave Type Variation on Tensile and Tearing Strength of Woven Fabric - Asaduzzaman, Md.; Mukibul Hasan, A.k.m.; Mohsin Patwary, Md; Mahmud, Shakil; Ariful Islam, Md; Hossain Raju, Tarek; Hossen, Afjal (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Among the functional properties of fabric, Tear & Tensile strength has the paramount importance and weave variation has a significant effect on this. The effect of a weave on the strength of the fabric is discussed in this research. For this purpose, five weave variations on a piece of fabric were woven having the same construction by using the Air Jet loom. Titan 5 Universal Tester was used for testing and previous works took under consideration. These results are presented in this paper with numeric value tables and graphs.